Analisisi Perspektif Mahasiswa pada Penerapan Kertas Kerja ATLAS di Era Digital - Kelvin Bagus Anugrah (JIATAX (Journal of Islamic Accounting and Tax), 2021)
The digital era demand that accounting students, the future of Indonesian’s auditor to adapt to the rapid change of time. Thus, in order to improve the quality of those future auditors, the Indonesian government designed ATLAS. From the government’s perspective, ATLAS was designed to digitalize and replace the old, obsolete audit working paper. But what about student’s perspectives of this digitalization? This research uses the Likert scale to answer that question. This research investigates student’s perspectives of the implementation of ATLAS as an audit working paper. We found that 78.18% of the students have a positive view/perspective of ATLAS implementation as an audit working paper.